Extracorporeal perfusion - reduced to a one-way infusion. - Taeger, Christian Dirk; Friedrich, Oliver; Horch, Raymund E.; Drechsler, Caroline; Weigand, Annika; Hopf, Fabio; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Wenzel, Carina; Geis, Sebastian; Prantl, Lukas; et al. (Clinical hemorheology and microcirculation, 2017)
BACKGROUND Extracorporeal perfusion (EP) is moving into focus of research in reconstructive and transplantation medicine for the preservation of amputates and free tissue transplants. The idea behind EP is the reduction of ischemia-related cell damage between separation from blood circulation and reanastomosis of the transplant. Most experimental approaches are based on a complex system that moves the perfusate in a circular course. OBJECTIVE AND METHODS In this study, we aimed to evaluate if a simple perfusion by an infusion bag filled with an electrolyte solution can provide acceptable results in terms of flow stability, oxygen supply and viability conservation for EP of a muscle transplant. The results are compared to muscles perfused with a pump system as well as muscles stored under ischemic conditions with a one-time intravasal flushing with Jonosteril. RESULTS With this simple method a sufficient oxygen supply could be achieved and functionality could be maintained between 3.35 times and 4.60 times longer compared to the control group. Annexin V positive nuclei, indicating apoptosis, increased by 9.7% in the perfused group compared to 24.4% in the control group. CONCLUSIONS Overall, by decreasing the complexity of the system, EP by one-way infusion can become more feasible in clinical situation